Orofacial Clefts: A Worldwide Review of the Problem. (20th May 2013) - Agbenorku, P.
Abstract : Orofacial cleft is one of the commonest congenital abnormalities which impacts negatively on the life of the individual and to a large extent affects the family. Caused by the interaction of environmental and genetic factors, this abnormality brings about decreased quality of life. Management of this abnormality entails a team involving a cleft surgeon, speech therapist, dentist, orthodontists, and so forth. This study involves the review of the various literatures on orofacial clefts, discussing the problems on the genetic basis, associated syndromes, and their management. Counseling of prospective mothers should be promoted to ensure that the abnormality is prevented at the early stages. Education on orofacial clefts should be promoted to create awareness on its preventive measures. Much attention must be geared towards cleft genetics studies to identify potential risk factors which might be predisposing individuals to the anomaly.